THE EFFECT OF POW + C-SPACE STRATEGY ONSTUDENT’S WRITING SKILL of NARRATIVE TEXT in MA NEGERI 4 TANJUNGPINANG - Disti Apriani; Elsa Ernawati Nainggola; Pradipta Agustina (Journal Of Language Education and Development (JLed), 2026)
The purpose of this study is to determine the effect of the POW + C-SPACE strategy on the ability of 11th-grade students at SMA Negeri 4 Tanjungpinang to write narrative texts. The students’ ability to develop ideas systematically, as well as inconsistencies in organizing the structure and linguistic elements of narrative texts, were the driving factors behind this study. This study employed a quantitative approach with a pre-experimental design involving a single group with pre- and post-tests. All 11th-grade students, comprising 12 classes with a total of 479 students, constituted the study population, while 37 students were selected as the sample using simple random sampling. Data were collected through pre- and post-treatment writing tests and analyzed using the Shapiro-Wilk test and the Wilcoxon Signed-Rank test. The results showed that a Z-value of –4.424 and a significance level of < 0.001 (p < 0.05) indicated a significant difference between pre- and post-test scores. Thus, the POW + C-SPACE strategy has a positive effect on improving students’ narrative writing skills. These findings imply that strategies based on systematic planning and the organization of ideas can be an effective alternative in teaching English writing at the secondary school level.